Resistance and backlash to gender equality. Issue 3 (1st October 2020) - Flood, Michael; Dragiewicz, Molly; Pease, Bob
Abstract: Resistance to efforts to advance gender equality is a common feature of social life, whether in workplaces and other organisations or elsewhere. In this article, we review the typical character, dynamics of and contexts for resistance to gender equality measures. Resistance is an inevitable, although undesirable, response to efforts at progressive social change. Backlash and resistance to gender equality take common forms including: denial of the problem, disavowal of responsibility, inaction, appeasement, co‐option and repression. Resistance may be individual or collective, formal or informal. Pushback against gender equality measures comes more often from members of the privileged group (men) than the disadvantaged group (women). Resistance is a predictable expression of the defence of institutionalised privilege, but it is also shaped by widespread discourses on "sex roles" and "post‐feminism, " the methods adopted to advance gender equality and the contexts in which they take place. Understanding the character and dynamics of resistance and backlash is vital for preventing and reducing them.